New discoveries in Eastern Mediterranean mesophotic sponge grounds: updated checklist and description of three novel sponge species - IDAN, TAL; SHEFER, SIGAL; FELDSTEIN, TAMAR; ILAN, MICHA (Mediterranean Marine Science, 2021)
Rich and diverse mesophotic sponge grounds were recently discovered along the easternmost part of the Mediterranean Sea (Israeli coast). Six sites have been surveyed over the last decade (2009-2019) and the sponge specimens discovered and collected in these expeditions have increased the known sponge richness of the Israeli fauna by 34%. Here we provide an updated checklist along with the distribution of the various species in seven mesophotic sponge grounds along the coast. Nine mesophotic species have been added, seven of which are new to the Israeli coast. Moreover, we describe three novel species: Hemiasterella verai sp. nov., Axinella venusta sp. nov., and Plakortis mesophotica sp. nov. H. verai sp. nov. differs from other congeneric species in both shape and color; in addition, it has thinner megascleres with more abundant oxeas and microscleres containing both oxyasters and strongylasters. A. venusta sp. nov. is a rather stiff and smooth axinellid with only a few short protruding spicules, and differs from other congeneric species mainly in shape and color. P. mesophotica sp. nov. is characterized by many folds and grooves, and molecular analysis revealed only a 96% similarity with Plakorits simplex.The discovery of these novel species highlights the importance of studying ecosystems that are not readily accessible. Further research of these mesophotic sponge grounds is needed in order to establish the community baseline data and support conservation attempts for these unique habitats.